Palaeomagnetism and magnetic fabric in the Freetown Complex, Sierra Leone - Hargraves, R. B.; Briden, J. C.; Daniels, B. A. (Geophysical Journal International, 1999)
About six separately orientated cores were collected at each of 14 sites distributed throughout the arcuate, west-dipping, 6 km thick, Freetown layered igneous complex. Alternating field and thermal demagnetization both isolate a stable component of remanent magnetism which corresponds to a palaeomagnetic south pole from 13 sites (nine reverse, four normal polarity) at 82.9°S, +32.7°E ( α 95 =5.6°). This is indistinguishable from that reported in 1971 based on alternating field demagnetization of cores from 10 orientated hand samples. The difference between the Freetown pole (age: 193±3 Ma) and other mid-Jurassic poles from West Africa could be due to its greater age. The difference between the whole West African Jurassic pole group and the Karoo pole from southern Africa, however, suggests moderate (∼10°) differential rotation of West Africa relative to the Kaapvaal craton. A prevalent magnetic foliation fabric coincides generally with the petrological layering, as might be expected, but a ubiquitous magnetic lineation is predominantly down-dip. This is compatible with a down-dip pyroxene lineation reported to be present in some field outcrops, and interpreted in terms of late-stage deformation during the slow crystallization and cooling of the large igneous body. However, a fold test shows that the igneous layering had already achieved its present attitude before the Complex cooled to ∼570 °C (the maximum blocking temperature of the characteristic remanence).